Hemoglobin M-Saskatoon clarified at molecular level by DNA sequencing of the 13-globin gene - Purnomo Suryantoro Purnomo Suryantoro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1998)
DNA sequencing of the 0-globin gene was done and clarify the Hemoglobin M-Saskatoon at molecular level.A boy was detected to suffer from 13-thalassemia since three year old. At four years of age, he underwent splenectomy due to severe splenomegaly. At 10 years of age blood sample was withdrawn and enzymatic sequencing of blood lympocyte DNA showed a mutation at Codon 63 (CAT->TAT). Therefore, hemoglobin M-Saskatoon was diagnosed. This mutation was also found in his mother detected by using NLA Ill restriction enzyme which digests the wild type of DNA at the CATG/region. This is the first report to demonstrate sequencing technique identifying hemoglobin M instead of using the biophysical examination of the blood oxygen binding affinity.Key words: /3-thalassemia - hemoglobin M - Saskatoon - DNA sequencing - endonuclease restriction enzyme